Penerapan Prinsip Keadilan Dalam Pemberian Ganti Rugi Atas Pembebasan Lahan Pertanian Untuk Pembangunan Jalan Umum : (Studi Kasus Di Kecamatan Sandubaya Kota Mataram) - Mega Mustika; Arief Rahman (Fakultas Hukum Universitas Mataram, 2022)
This research aims are to know the implementation of just principle towards agricultural land acquisition for public road, and also to know supporting and inhibiting factors during the process of land acquisition for the development of Tegal to Gontoran road in Sandubaya. Type of this research is empirical legal research which applies statute, conceptual and sociological approaches. land acquisition for 20 area of rice fields with 16 owners conducted by discussion. The compensation values rise rejection from the land owner, but eventually they are close the arrangement, land owner and government through discussion. In addition, supporting and inhibiting factors are consist of juridical and non-juridical.